Arrhythmia and/or Cardiomyopathy Related to Maternal Autoantibodies: Descriptive Analysis of a Series of 16 Cases From a Single Center - Wang, Benzhen; Hu, Sujuan; Shi, Degong; Bing, Zhen; Li, Zipu (Frontiers in Pediatrics, 2019)
Objective: To describe the clinical characteristics of maternal autoantibody-mediated arrhythmia and/or cardiomyopathy, and to explore the therapeutic role of glucocorticoids in these diseases. Methods: This was a retrospective observational study of 2 fetuses and 14 children who presented with autoantibody-mediated arrhythmia and/or cardiomyopathy in our hospital from September 2010 to December 2018. Results: In total, 16 patients were identified, including 2 fetuses, and 14 children. One mother suffered from Sjogren's syndrome, two suffered from systemic lupus erythematosus (SLE), and the remaining 13 were asymptomatic carriers of autoantibodies. Two fetuses were diagnosed with complete congenital heart block (CHB) and had mean heart rates of 45 and 50 bpm. In the 14 surviving children, third-degree CHB was detected in 4 children, second- to third-degree CHB in 4, corrected QT interval (QTc) prolongation in 1, atrioventricular dissociation, and junctional ectopic tachycardia in 1, complete left bundle branch block (CLBBB) with dilated cardiomyopathy (DCM) in 3, and endocardial fibroelastosis (EFE) in 1. All of the 14 surviving babies received intravenous immunoglobulin and glucocorticoids. None of the children received pacemaker implantation. During the follow-up, one 3-month-old girl who had complete CHB, DCM, and Torsades de pointes almost recovered after the administration of prednisone for ~8 years. Three cases with complete CHB had no improvement after 3–5 years of follow-up. One case with EFE and three cases with CLBBB and DCM were in stable condition now. Children with QTc prolongation and junctional ectopic tachycardia returned to a regular rhythm. Conclusions: Autoantibody-mediated arrhythmias and/or cardiomyopathy are severe complications related to maternal autoantibodies, and the administration of steroid may be beneficial in reversing complete CHB.